Dyeing with extracts from Amaranth plant - Hwanhee Lee; Boris Mahltig (Communications in Development and Assembling of Textile Products)
Amaranth is a red colored crop planted as alternative food source. The use of red dye from Amaranth as food colorant and other applications is well described in literature. In contrast, the application of Amaranth for textile dyeing purposes is less described. For this, the actual paper reports an extraction process from Amaranth and the application on textile fabrics. Different mordanting processes are considered. As well the fluorescent properties of Amaranth extract are determined but a transfer of fluorescence properties on the dyed fabrics is not observed. In respect to realized color intensity, the use of iron sulphate based mordant is superior compared to alum based mordant or dyeing without mordanting. However, the red coloration of Amaranth turns into brown and greyish coloration after application onto the fabric. Suitable washing and rubbing fastness are reached. Finally, it can be stated that textile dyeing with aqueous extract from Amaranth is possible but due to the change of the attractive red coloration into brownish color shades during dyeing process, the use in textile coloration is obviously limited